A Heart Rate Step Function Response Method for the Evaluation of Pulse Wave Velocity as a Predictor of Major Adverse Cardio-Vascular Events - Marin, Ioana; Popescu, Florina Georgeta; Pauncu, Elena-Ana; Apostol, Adrian; Ivan, Viviana Mihaela; Marin, Catalin Nicolae; Fira-Mladinescu, Ovidiu; Ursoniu, Sorin (Medicina (Kaunas, Lithuania), 2022)
Background and Objectives: Cardiovascular diseases are the main cause of death worldwide, and pulse wave velocity (PWV) is considered a predictor of major adverse cardiovascular events. The study intended to be helpful in finding methods for the preliminary assessment of PWV in primary care units. Materials and Methods: The study group consisted of 36 subjects (considered healthy by their own statement) from the medical field (medicine students and residents) aged between 20 and 30 years: 33.3% males and 66.7% females. Two types of measurements were carried out successively: (a) measurements with the arteriograph and (b) measurements on a treadmill effort testing system, where heart rate (HR) was measured over time as a response to step function physical effort (PE). Results: The study allowed for the highlighting of some limits which, if exceeded, can be associated with high PWV values: (i) if after a moderate PE and a resting time of at least 6 min, the HR is larger than 80 b/min; (ii) if the relaxation time in a PE test of moderate intensity is larger than 1 min; (iii) if the HR measured after the subject is raised from the supine to orthostatic position is larger than 100 b/min, and (iv) if the resting HR is larger than 80 b/min. Conclusions: Steady-state HR correlates with PWV and may be used for the preliminary assessment of PWV.